Experiences of empathy and literary empathy between children using the LuDiCa (dialogic reading for deep comprehension) - Rogoski, Bianca da Nóbrega; Pfeiffer-Flores, Eileen (Frontiers in Psychology, 2025)
This study investigated the effects of the shared reading technique LuDiCa (Dialogic Reading for Deep Comprehension) on interpersonal and literary empathy among school-age children. In the LuDiCa method, a pre-reading analysis of the story leads to the preparation of open-ended questions that are used during shared reading with children. Unlike traditional dialogic reading, these questions are carefully designed to foster deep comprehension by guiding discussion around narrative functions. Narrative functions are what the story shows the reader through events, dialogues, descriptions and other elements, often implicitly. Twelve children participated in LuDiCa sessions of stories about immigrants and refugee children. LuDiCa significantly promoted expressions of both interpersonal empathy among participants and literary empathy toward immigrant and refugee characters. The findings suggest that interactive group reading sessions using the LuDiCa method can effectively enhance empathy, contributing to a deeper understanding of diverse human experiences.